(untitled) (Journal of Enam Medical College, 2018)
Background: Fibrocystic breast condition is a common, non-cancerous condition that affects premenopausal woman between 20 and 50 years of age. Because of non-specific nature of clinical presentation, diagnosis is not that easy. Linear array sonography has been helpful for detection of mammary dysplasia. Objective: The purpose of this study was to determine the sensitivity, specificity, accuracy, positive predictive value and negative predictive value of superficial sonography in the diagnosis of chronic cystic mastitis. Materials and Methods: This study was carried out in department of Radiology & Imaging of Enam Medical College and Hospital during June 2013 to October 2017. Sonography was done in 1350 women suspected of having fibrocystic disease. Among them FNAC was done only in 1020 cases. Ultrasonographic findings and histopathological reports were analyzed using SPSS 13.0. Results: According to our study the sensitivity of superficial sonography was 92.4%, specificity 88.8%, positive predictive value 93.8%, negative predictive value 86.4% and accuracy 91% in the diagnosis of fibrocystic changes.Conclusion: With the validity test result, it can be concluded that high frequency sonography provides an accurate diagnosis of fibroadenosis. J Enam Med Col 2018; 8(3): 139-143